An isogeometric analysis approach for solving the Reynolds equation in lubricated piston dynamics. (November 2016) - Liu, Wei; Huang, Zhengdong; Liu, Qinghua; Zeng, Jiani
Abstract: This paper discusses the approach of isogeometric analysis (IGA) for solving the Reynolds equation in lubricated piston dynamics. The simulation model consists of two parts: the differential-algebraic equations (DAE) in piston dynamics and the Reynolds equation for lubrication of piston-cylinder interface. Here, the transient positional states of piston governed by the DAE are calculated in Dymola while the friction forces together with lateral forces and their moments are computed by solving the Reynolds equation with the IGA approach in Matlab; two parts of computation are integrated through a real-time communication program. The results show that the efficiency is improved remarkably than the traditional Finite Element Method (FEM) when the IGA approach is adopted. Highlights: The piston dynamic system is built with a consideration of the inertia forces of connecting rod and crankshaft. The approach of isogeometric analysis is proposed for solving the Reynolds equation. An intermediate data reuse method is presented for calculating the stiffness matrix. Numerical comparisons with the traditional approach are provided.